التفسير الصوفي الإشاري في بداية السالكين:دراسة نقدية في روح البيان للبروسوي - Mahyuddin Hashim; Abdul Rahman Hussein Obeid; Adnan Mohamed Yusoff (Universiti Sains Islam Malaysia, 2024)
This research aims to define Tafsir Sufi Ishari and Tafsir Ruhul Bayan by Al-Burusawi (1715). The research as well will extrapolate Tafsir Sufi Ishari for Quranic verses in the book related to the issue of the Madarij al-Salikin (scales of seekers) in Sufism. The methodology for this research in analyzing information depends on the descriptive and criticism approach. Therefore, the findings indicate that the Tafsir Sufi Ishari – which is One of the types of the Quranic exegesis based on interpretations of verses contrast the classical commentaries - by Al-Burusawi in the issue of the Madarij al-Salikin (scales of seekers) in Sufism that matching the conditions were based on two foundations. Firstly: The Tafsir Sufi Ishari has interpreted accordingly to general verses meaning and exegesis. Secondly: The relationship between Tafsir Sufi Ishari to al-Ma'thur is like the relationship between cause and effect. The study also revealed that the contradictions with conditions in Tafsir Sufi Ishari in this issue are based on three foundations. Firstly: The interpretations made were analogous compared to other normal exegeses. Secondly: to generalize some issues which are strictly individuals. In fact, if Al-Burusawi limited his interpretation to his Ishari views there are no differences between him and the doctrine of Shiites Batiniyyah!, But our trust in his scholarly Tafsir, his confirmation of classical interpretation and his condemnation of Batiniyyah understanding make his Tafsir Ishari valid and well concerned.